The Development of the Filipino Coping Strategies Scale - Rilveria, John Robert C. (Animo Repository, 2018)
The development of the Filipino Coping Strategies scale was based on the qualitative data on the resilience of Filipinos and the ways by which they cope with stressful life experiences and the quantitative data on foreign measures of coping. Integration of both data led to the formulation of nine coping strategies: cognitive reappraisal (pagsusuri), social support (paghingi ng tulong), problem-solving (pagtugon), religiosity (pagkarelihiyoso), tolerance (pagtitiis), emotional release (paglabas ng saloobin), overactivity (pagmamalabis), relaxation/recreation (paglilibang), and substance use (pagbibisyo). Initially, the scale was composed of 45 items with five items under each domain. This was pilot tested to 627 male and female Filipinos aged 18 above. Reliability analysis revealed items that are internally consistent with each other resulting in the reduction of items to 37. Furthermore, construct validity was established via a) factor analysis through principal components analysis extraction method and varimax rotation method and b) test for convergent validity by correlating each domain of the Filipino Coping Strategies scale with the corresponding domains of Ways of Coping by Folkman and Lazarus and the COPE Inventory by Carver, Scheier, and Weintraub. Independent samples t-test revealed significant differences among males and females in each coping strategy which served as the basis for norm groups. The Filipino Coping Strategies scale is a four-point Likert scale which aims to measure the coping strategies of Filipinos towards stress and generates a coping dispositional profile which can be used to aid in the assessment of coping behaviors.